Exploring the caffeine-induced teratogenicity on neurodevelopment using early chick embryo. - Zheng-lai Ma; Yang Qin; Guang Wang; Xiao-di Li; Rong-rong He; Manli Chuai; Hiroshi Kurihara; Xuesong Yang (PLoS ONE, 2012)
Caffeine consumption is worldwide. It has been part of our diet for many centuries; indwelled in our foods, drinks, and medicines. It is often perceived as a "legal drug", and though it is known to have detrimental effects on our health, more specifically, disrupt the normal fetal development following excessive maternal intake, much ambiguity still surrounds the precise mechanisms and consequences of caffeine-induced toxicity. Here, we employed early chick embryos as a developmental model to assess the effects of caffeine on the development of the fetal nervous system. We found that administration of caffeine led to defective neural tube closures and expression of several abnormal morphological phenotypes, which included thickening of the cephalic mesenchymal tissues and scattering of somites. Immunocytochemistry of caffeine-treated embryos using neural crest cell markers also demonstrated uncharacteristic features; HNK1 labeled migratory crest cells exhibited an incontinuous dorsal-ventral migration trajectory, though Pax7 positive cells of the caffeine-treated groups were comparatively similar to the control. Furthermore, the number of neurons expressing neurofilament and the degree of neuronal branching were both significantly reduced following caffeine administration. The extent of these effects was dose-dependent. In conclusion, caffeine exposure can result in malformations of the neural tube and induce other teratogenic effects on neurodevelopment, although the exact mechanism of these effects requires further investigation.